Kajian Hukum Terhadap Putusan Mahkamah Konstitusi Nomor: 013/PUU-I/2003 - Anwar Cengkeng (Universitas Widya Gama Malang, 2022)
One of the powers of the Constitutional Court according to the 1945 Constitution is to examine the constitutionality of laws. Examination of Law no. 16 of 2003 on the 1945 Constitution by the Constitutional Court In general it has reflected the concept of people's sovereignty and the rule of law, but the interpretation made by the Constitutional Court on the meaning of Article 28I and Article 28J is still partial, even though the history of the formulation of the two Articles is intended as a package, namely the enactment of Article 28I. limited by the entry into force of Article 28J.